Comprehensive hematological reference intervals in a healthy adult male population - Ghazizadeh, Hamideh; Kathryn Bohn, Mary; Kardagh Polus, Ranan; Abdulkarimi, Rahim; Mahdavizadeh, Vahid; Ghaffarian Zirak, Roshanak; Kamel Khodabandeh, Atieh; Zare-Feyzabadi, Reza; Timar, Ameneh; Mohammadi-Bajgiran, Maryam; Oladi, Mohammad Reza; Esmaily, Habibollah; et al. (Cellular and Molecular Biology, 2020)
Reference intervals (RIs) are important tools for improving medical decision-making. Hematology reference values can be influenced by important covariates such as genetic and environmental factors, rendering it essential to define RIs for specific populations. Therefore, we aimed to establish accurate and robust RIs for hematological markers in a healthy adult male Iranian population. This cross-sectional study was conducted in a population of 723 males aged 20-60 years old. Hematological parameters were routinely measured using a Sysmex auto analyser system (KX-21 N). The quality of assays was monitored using commercial quality control samples. The nonparametric rank method, as recommended by the Clinical and Laboratory Standards Institute (CLSI) guidelines, was used to calculate the 2.5th and 97.5th percentiles as the lower and upper reference limits, respectively. Of the 12 hematological parameters assessed, only mean platelet volume (MPV) demonstrated significant age-specific differences, requiring two partitions from 20 to 35 years (8.7-12.2 fL) and 35 to 65 years (8.5-11.5 fL). The remaining hematological parameters (e.g. leukocyte, erythrocyte, and platelet parameters) could be defined by one age range. This study established RIs for 12 routinely used hematological parameters in a healthy male population living in the northeastern region of Iran. Established RIs differed from those previously reported by other cohorts, highlighting the importance of population-specific RIs.